Océan Austral - Iles de Kerguélen, baie du Morbihan (partie est) / d'après le levé exécuté en 1949-1950 . Service hydrographique de la marine . 1952 - France. Service hydrographique de la marine; (Paris : Service hydrographique de la marine, 1955)
Publication Octobre 1952. Corr. . 1955 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in purple Color; 1:30,000